Peranan Mahasiswa KKN Dalam Kegiatan Pengembangan UMKM Di Desa Bojongmangu Melalui Branding Dan Redesain Produk - Muhamad Rizki Akbar; Iswar Dian Tama; Ayu Dinda Lestari; Silvia Suci Noviandini; Sekar Monica Pramestia Putri; Okka Chandra Pitaloka; Yuni Inayah; Ambar Sri Wiyatiah (CV. ITTC INDONESIA, 2024)
Real Work Lecture or commonly called KKN is one of the programs that students must do as a form of self-service to the community. This KKN was curried out in Bojongmangu Village, Bojongmangu District for 30 days, from July 28 to August 27, 2024. The purpose of this KKN activity is to see the role of KKN students in MSME development activities in Bojongmangu Village. This research uses a qualitative method, with observation techniques and direct assistance. The result of this study is that KKN students can actively contribute to helping improve the product branding of MSMEs.